Projecting spatiotemporal variations of sunshine duration with regards to climate change in Iran as a step towards clean energy. (October 2022) - Ghanghermeh, Abdolazim; Roshan, Gholamreza; Halabian, Amirhossein
Graphical abstract: Highlights: Climate change in the coming decades will reduce the diversity of sundial clusters in Iran. Findings show that global warming will increase Iran's sundial. Latitude is important factor in the spatial variability of Iran's sundial is latitude. Abstract: Iran is a country with great potential for using solar energy. To manage the supply and demand for using solar energy technologies, proper knowledge regarding the areas with homogeneous sunshine duration is essential. Therefore, in this study, the monthly data anomalies were used to determine homogeneous climatic regions over two study periods. The matrix grids were prepared for the base (1981–2018) and future (2041–2080) periods respectively as 456×272 and 480×272 (the number of months and stations). Notably, the future period model was prepared according to two separate Representative Concentration Pathway (RCP) scenarios (4.5 and 8.5). The S-mode input matrix was used to perform principal component analysis (PCA) and Ward's method was utilized for cluster analysis (CA). Subsequently, the stations were partitioned into different sunshine clusters. Findings showed that 86.6 % of the total variance were involved with seven leading PCs (7 clusters for the base period), 67.2 % with four initial RCP4.5 components, and 62.8 % with the first three RCP8.5 components (4 and 3 clusters for the future period, respectively). Concerning the sunshine duration, results indicated geographical latitude as the most important factor for the spatial distribution of different clusters. Additionally, global warming was seen to have caused an increase in sunshine hours for 73 and 182.5 hr/year according to RCP4.5 and RCP8.5 compared to the base period. Therefore, an overview of how climate change could affect sunshine duration in Iran enhances the potential for efficient use of clean solar energy.